Unmaking the Modern Man: Masculinity, Materialism, and Resistance in Fight Club - Syahruna, Sultan; Maulidya, Reza Anis (Universitas 17 Agustus 1945 Semarang, 2025)
Directed by David Fincher, Fight Club (1999) presents a complex and provocative critique of consumer culture, masculinity, and resistance within a postmodern capitalist society. This study examines how the film constructs and destabilizes male identity by employing an integrated framework of Critical Discourse Analysis (CDA) and Multimodal Discourse Analysis (MDA). Using Fairclough’s three-dimensional model and Kress and van Leeuwen’s multimodal theory, the analysis focuses on how ideological meanings are produced through the interaction of linguistic discourse and cinematic techniques. The findings reveal that consumerism reduces identity to a market-driven commodity, while masculinity is represented as fragmented, unstable, and continuously negotiated through discourse and visual symbolism. Acts of resistance, particularly those embodied by Fight Club and Project Mayhem, are shown to function as contradictory forms of liberation that ultimately reproduce new structures of control. By analyzing dialogue, narration, visual imagery, sound design, and mise-en-scène, this study demonstrates that masculinity in Fight Club operates not merely as a narrative theme but as a discursive formation shaped by power relations across multiple semiotic modes. This research contributes methodologically to film discourse studies by highlighting the analytical value of integrating CDA and MDA in examining ideology, identity, and resistance in contemporary media texts. Keywords: Fight Club, Masculinity, Materialism, Resistance, Critical Discourse Analysis, Multimodal Discourse Analysis